Kajian Literatur Distribusi Kompensasi Dampak Tempat Pengelolahan Sampah Terpadu (Tpst) Bantargebang: Analisis Keadilan Distributif Dan Keadilan Sosial - Tamba, Wahyu Pratama (Jurnal Ilmu Kesejahteraan Sosial, 2024)
The waste problem in Jakarta is a complex issue related to the large volume of waste, dependence on Bantargebang TPST, and the various environmental impacts caused. Waste from Jakarta brought to Bantargebang TPST reaches 6,500-7,000 tons daily. This TPST hurts the environment and the health of the surrounding community, as well as the risk of ARI, air pollution, groundwater pollution, and environmental aesthetics. As compensation for these negative impacts, the DKI Jakarta Provincial Government allocates compensation funds for affected communities. This is regulated in Article 10 letter (e) of DKI Jakarta Regional Regulation number 4 of 2019 which states that the community has the right to obtain compensation for the negative impact of waste landfills. Furthermore, the distribution, distribution, and criteria for compensation beneficiaries are regulated in the Cooperation Agreement (PKS) between the Governor of DKI Jakarta the Mayor of Bekasi, and the Bekasi City Environment Agency Work Plan (Renja) for 2021. This research aims to describe compensation in DKI Jakarta's waste management policy along with its distribution and highlight related regulations. This research is designed with a qualitative approach, the method used is a literature study, namely research journals, books, reviewing regulations, official government reports, and media coverage. The results show that the distribution of compensation has not been fully effective in improving the welfare of affected communities. This research fills the knowledge gap on Bantargebang TPST compensation distribution and offers a new analysis of waste management policy in DKI Jakarta from the perspective of social welfare science and social policy studies.